Effect of Work Environment and Workload on Employee Performance - Muslih Muslih; Farhan Anshari Damanik (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
The purpose of this research is to determine and analyze the effect of the work environment and workload on performance at PT. Perkebunan Nusantara IV (Persero) Medan either partially or simultaneously.The approach used in this study is an associative approach. The population in this study were all employees PT. Perkebunan Nusantara IV (Persero) Medan. The sample in this study using the slovin formula totaling 81 employees atPT. Perkebunan Nusantara IV (Persero) Medan. Data collection techniques in this study used interview techniques, documentation studies, observation, and questionnaires. The data analysis technique in this study uses Multiple Linear Regression Analysis Test, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. The data processing in this study used the SPSS (Statistical Package for the Social Sciences) software program version 24.00. The results of this study prove that partially and simultaneouslywork environment and workload have a significant effect on employee performance at PT. Perkebunan Nusantara IV (Persero) Medan.